FISHERIES PRODUCT SPOILED MONITORING USING SMART PACKAGING CONTAIN ANTHOCYANIN: A REVIEW - Hamidah, Syalyva; Abdillah, Annur Ahadi; Sulmartiwi, Laksmi (Universitas Mataram, 2025)
Smart packaging is currently demanded to monitor the spoilage level of packaged products, for instance fishery products, characterized as perishable food. Smart packaging requires a halochromic substance, for instance, natural pigments extracted from fruits or flower. The natural pigment extracted from the plant should have a halochromic ability for example anthocyanins compound. Anthocyanin compounds are incorporated to edible film to produce smart film. The smart film has the ability to screen the quality and to monitor freshness of fishery products by demonstrating color changes from purple or blue to green and then yellow color after being exposed to spoiled conditions. The color changes are induced by changes of pH and TVB-N production in deteriorated of packaged fishery products. Moreover, smart packaging is able to provide real-time information to consumers regarding product freshness, thus enhancing the safety and maintaining the quality of food products. In addition, the advantages of a smart packaging system include simple and inexpensive production, providing